An Empirical Analysis of an Incentive Plan with Relative Performance Measures: Evidence from a Postal Service - Matsumura, Ella Mae; Shin, Jae Yong (The Accounting Review, 2006)
Using 1997–1999 annual performance evaluation data of 214 postal stores in Korea, we find that financial performance improves following the implementation of an incentive plan that includes relative performance measures, and that under this incentive plan, the degree of common uncertainty is positively associated with store profitability. We also find evidence that the incentive effect of the plan is mitigated in stores at which the employees' perceived unfairness is likely to be high. Finally, we find that the net benefits of introducing the incentive plan may be conditional on the degree of common uncertainty, which appears to be inversely related to the perceived unfairness attributable to the introduction of the contract with relative performance measures.